Contrasting effects of the α7 nicotinic receptor antagonist methyllycaconitine in different rat models of heroin reinstatement. (October 2021) - Palandri, Josephine; Smith, Sharon L; Heal, David J; Wonnacott, Sue; Bailey, Chris P
Background: α7 Nicotinic acetylcholine receptors are implicated in the reinstatement of drug-seeking, an important component of relapse. We showed previously that the α7 nicotinic acetylcholine receptor antagonist, methyllycaconitine, specifically attenuated morphine-primed reinstatement of conditioned place preference in rodents and this effect was mediated in the ventral hippocampus. Aims: The purpose of this study was to evaluate α7 nicotinic acetylcholine receptor antagonism in reinstatement of the conditioned place preference for the more widely abused opioid, heroin, and to compare the effect of α7 nicotinic acetylcholine receptor blockade on reinstatement of heroin-seeking and heroin self-administration in an intravenous self-administration model of addictive behaviour. Methods: Rats were trained to acquire heroin conditioned place preference or heroin self-administration; both followed by extinction of responding. Methyllycaconitine or saline was given prior to reinstatement of drug-primed conditioned place preference, or drug-prime plus cue-induced reinstatement of intravenous self-administration, using two protocols: without delivery of heroin in response to lever pressing to model heroin-seeking, or with heroin self-administration, using fixed and progressive ratio reward schedules, to model relapse. Results: Methyllycaconitine had no effect on acquisition of heroin conditioned place preference or lever-pressing for food rewards. Methyllycaconitine blocked reinstatement of heroin-primed conditioned place preference. Methyllycaconitine did not prevent drug-prime plus cue-induced reinstatement of heroin-seeking, reinstatement of heroin self-administration, or diminish the reinforcing effect of heroin. Conclusions: The α7 nicotinic acetylcholine receptor antagonist, methyllycaconitine, prevented reinstatement of the opioid conditioned place preference, consistent with a role for α7 nicotinic acetylcholine receptors in the retrieval of associative memories of drug liking. The lack of effect of methyllycaconitine in heroin-dependent rats in two intravenous self-administration models suggests that α7 nicotinic acetylcholine receptors do not play a role in later stages of heroin abuse.